SUPERVISI AKADEMIK KEPALA SEKOLAH SMA NEGERI DI KOTA TERNATE - Mukhtar Yusuf; Jainudin Abdullah; Mansur Hasan (EDUKASI, 2022)
The purpose of this study was to analyze (1) the implementation of academic supervision of the principals of public high school in Ternate; (2) the obstacles are faced by the principals of public high school in Ternate in carrying out academic supervision and (3) the principals' have an efforts to overcome the obstacles in implementing academic supervision in Public High Schools in Ternate. The approach in this research is qualitative. Data sources: principals, teachers and students. The results of this study indicate that (1) the implementation of academic supervision by the principal of a public high school in Ternate carried out simultaneously according to their functions and roles as supervisors. Activities carried out by school principals as supervisors include developing and strengthening teacher competency capacities within the scope of curriculum development, teaching and learning processes, solving teaching difficulties, teacher mediation in solving teacher and student problems in schools, (2) the obstacles are faced by the principals of  public high school in Ternate to implementing academic supervision is the limited time for the principal in escorting and fostering teachers during the implementation of learning in the classroom, limited school facilities and infrastructure . In addition, some teachers are reluctant to be supervised, they view that supervision is still considered as an effort to reveal the weaknesses of teachers in carrying out their duties and (3) an effort to overcome obstacles in the implementation of academic supervision by principals of public high school in Ternate is to carry out academic strengthening, such as training to increase teachers’ Professional competence and pedagogical teachers in order to improve the quality of education.